Undvigestrategier – en tilføjelse til europæiseringslitteraturen - Kjærgaard, Nikoline Holm (Politik, 2011)
Despite a large literature on Europeanization, we still know relatively little about how civil servants act in those instances where national policy conflicts with EU-law. This article examines this gap in the knowledge by developing taxonomy of evasion strategies that national actors may apply in an attempt to resist change inflicted upon national policy by the EU. They are: a) Up-loading; b) Use of veto points; c) Communica- tion; d) Issue-linking; e) Implementation. These evasion strategies are derived from a screening of existing Europeanization studies. The article applies the taxonomy of evasion strategies to a case study of Denmark’s implementation of Directive 2004/38/EC on freedom of movement in the EU, and argues that civil servants to a large extent made use of such evasion strategies.